Control de las funciones operativas de un Departamento de Ingeniería Biomédica - García Martínez, A. L. (Revista Mexicana de Ingenieria Biomedica, 2007)
Quality in health services is the main objective for healthcare institutions. This means not just to correct adverse events but preventing them, as the concept of total quality approach establishes. In this sense, the objective of a Biomedical Engineering Department (BED) in a Hospital, is to maintain the medical equipment in optimal conditions of functionality as well as the hospital facilities, because of these elements has an important impact in the health services quality. The objective of this work was to develop and to apply some control forms, in order to provide information about the performance of the technical personnel of the BED, as well as maintenance processes done by the BED from the Child’s Hospital of Sonora State, improving the performance level of the personnel and helping in health services quality.